Magnesium, zinc, and chromium nutrition and athletic performance - Lukaski, H. C. (Canadian Journal of Applied Physiology, 2001)
Magnesium, zinc and chromium are mineral elements required in modest amounts for health and optimal performance. Accumulating evidence supports the hypothesis that magnesium and zinc play significant roles in promoting strength and cardiorespiratory function in healthy persons and athletes. Differences in study designs, however, limit conclusions about recommendations for intakes of magnesium and zinc needed for optimal performance and function. The role of chromium in supporting performance is not well established. There is a compelling need to confirm and extend findings of beneficial effects of magnesium and zinc function and performance of humans. Suggestions for an experimental model and specific topics for research to advance knowledge of mineral nutrition to promote attainment of genetic potential for optimal performance are provided.